Studies on Fly- ash and Slag incorporated Sustainable AAC Composites - Verma Shivangi; Yadav Amit; Kumar Rajesh; Kulkarni Kishore S.; Khan Shahnavaz (E3S Web of Conferences)
Autoclaved aerated concrete (AAC) is a lightweight and environmentally friendly construction material that is being utilized in modern masonry construction. This paper presents the development of AAC, consisting of industrial wastes such as Class F fly ash and Ground Granulated Blast-furnace Slag (GGBS). In this study, the AAC was composed of OPC, GGBS, fly ash, water, and aluminum oxide (which generates hydrogen bubbles). AAC blocks were manufactured by combining, shaping, slicing, and autoclaving at elevated temperatures and pressures, as per IS 2185 (Part 3). AAC samples were developed by substituting sand with fly ash or GGBS at four different levels: 25%, 50%, 75%, and 100%. After the autoclave process, the flexural, compressive, and thermal conductivity properties of all AAC samples were analyzed. The microstructure was analyzed using optical microscopy (OM) and X-ray diffraction (XRD). The densities of all AAC samples ranged from 450 to 650 kg/m3. The compressive strength of the fly ash-induced AAC samples varied from 1.6 to 2.2 MPa, while the thermal conductivity ranged from 0.147 to 0.164 W/mK. The compressive strength of GGBS incorporated AAC composites ranged from 0.78 to 3.24 MPa, thermal conductivity ranged from 0.151 to 0.162 W/mK, and flexural strength varied from 0.30 to 1.17 MPa. AAC has a lower energy consumption than clay bricks. In conclusion, autoclaved aerated concrete is a versatile and sustainable building material that offers a range of benefits, including reduced density, increased specific strength, improved thermal insulation, and enhanced fire resistance, when compared to conventional concrete. Their unique properties make them an attractive option for modern construction projects.